Academic Senate Minutes 2002-02-21 - Academic Senate:::::::::
Addition of Agenda item failed. Minutes approved. Report from Chair. All three Senate Budget committee resolutions tabled. Amended Evaluation of Temporary Faculty procedures tabled. Structures and Functions bylaw amendment resolution on first and second readings approved. Bylaw amendment resolution on Secretary duties and proposal for faculty governance release time units distribution tabled. Reports from Provost, Vice President of Administration and Finance, Chair-Elect, Associated Students, Statewide Senator, and APC.